Dual-Energy CT: Balance Between Iodine Attenuation and Artifact Reduction for the Evaluation of Head and Neck Cancer. Issue 6 (November 2017) - Nair, Jaykumar R.; DeBlois, François; Ong, Thomas; Devic, Slobodan; Tomic, Nada; Bekerat, Hamed; Rosenbloom, Lorne; Sultanem, Khalil; Forghani, Reza
Abstract : Objective: Dual-energy computed tomography high energy virtual monochromatic images (VMIs) can reduce artifact but suppress iodine attenuation in enhancing tumor. We investigated this trade-off to identify VMI(s) that strike the best balance between iodine detection and artifact reduction. Methods: The study was performed using an Alderson radiation therapy phantom. Different iodine solutions (based on estimated tumor iodine content in situ using dual-energy computed tomography material decomposition) and different dental fillings were investigated. Spectral attenuation curves and quality index (QI: 1/SD) were evaluated. Results: The relationship between iodine attenuation and QI depends on artifact severity and iodine concentration. For low to average concentration solutions degraded by mild to moderate artifact, the iodine attenuation and QI curves crossed at 95 keV. Conclusions: High energy VMIs less than 100 keV can achieve modest artifact reduction while preserving sufficient iodine attenuation and could represent a useful additional reconstruction for evaluation of head and neck cancer. Abstract : Supplemental digital content is available in the text.